Factors Associated with Obstetric Fistula Repair Failure among Women Admitted at Gynocare Women’s and Fistula Hospital in Kenya, 2012-2016: A Case Control Study - Mwang, Henry Ruiru; Wang'ombe, Ann; Mabeya, Hillary; Kipruto, Hillary; Wanjala, Anthony (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: To determine factors associated with obstetric fistula repair failure at Gynocare Women’s & Fistula Hospital in Kenya. Methods: This is a case-control study of patients who underwent fistula repair at Gynocare from January 2012 to December 2016. Total of 357 patients (119 cases and 238 controls) were taken by simple random sampling. Results: Study participants were mostly married (62.2%) with low or no formal education (90.1%). Delivery that led to fistula development occurred in the hospital for 85.2% of the study participants and 66.7% had Cesarean Section. Only one-third (120) had previous repair(s). Patients classified to have VVF IIA were 20.5%, class IIB were 35.0% and class III were 9.2%, and the rest (35.3%) were classified as class I. The odds of repair failure were 2.9 times more among those with previous repair attempts compared to those with no previous repair attempts. Women with VVF IIB were 4 times more likely to develop failure. While women who attained at least secondary education were 77% less likely to have fi stula repair failure. Conclusion: After controlling the eff ects of age, marital status, comorbidities, parity, time to repair, post-operative complications, having not attained at least secondary education level, having previous repair attempts, and VVF IIB were found to be independent predictors of repair failure. Key words: Failure, Kees Waaldjik, Obstetric Fistula, Obstetric Fistula Classifi cation, Repair